Comparative isolation of serum ? + pre- ? lipoproteins of human and various domestic animal species by dextran sulfate/MnCl2 and sodium phosphotungstate/MgCl2 precipitation methods - Ileri, Tülay; Güldür, Tayfun (My University, 2002)
Lipoproteins are water-soluble complexes through which various lipids are transported between the various tissues for storage and utilization. Association of lipoproteins with risk of coronary heart disease and various types of dyslipoproteinemias necessitate the quantification of the individual lipoprotein classes. The study was undertaken to compare the concentrations of precipitation reagents (dextran sulfate/MnCl2, sodium phosphotungstate/MgCl2) necessary in order to precipitate ?+pre-? lipoproteins in human and various animal sera. To this end, the serum ?+pre-? lipoproteins of human and various animal species were precipitated using various methods. The lipoproteins precipitated were separated and identified by agarose gel electrophoresis. Dextran sulfate/MnCl2 at the concentration used for human serum resulted in complete precipitation of ?+pre-? lipoprotein of sera from all animal species. In the sodium phosphotungstate/MgCl2 precipitation method, ?+pre-? lipoproteins of goat and sheep were precipitated by two times more sodium phosphotungstate/MgCl2 than that required for human serum ?+pre-? lipoproteins. Also in other animal species ?+pre-? lipoproteins were precipitated by the same sodium phosphotungstate/MgCl2 concentration. It was concluded that the concentrations of polyanion/divalent cation used for the precipitations of serum ?+pre-? lipoproteins differ between human and several animal species. The existing differences might be attributed to the variations in charge densities of lipoproteins' surfaces as well as to dissimilarities in lipid compositions of the lipoproteins between species.
İnsan ve bazi evcil hayvan türlerinin serum ? + pre- ? lipoproteinlerinin dekstran sülfat/MnCl2 ve sodyum fosfotungstat/MgCl2 presipitasyon metotlari ile karşilaştirmali i?zolasyonlari
Keywords: Divalent cation; Lipoprotein isolation; Polyanion; Precipitation; Serum